2013
DOI: 10.1002/anie.201208799
|View full text |Cite
|
Sign up to set email alerts
|

Fulvenes as Effective Dipolarophiles in Copper(I)‐Catalyzed [6+3] Cycloaddition of Azomethine Ylides: Asymmetric Construction of Piperidine Derivatives

Abstract: Catalytic asymmetric [3+2] cycloaddition of azomethine ylides is one of the best methods for constructing enantioenriched heterocyclic pyrrolidines, [1] and extensive studies have been conducted on the use of various electron-deficient alkenes as the 2p synthons over the past decade. [2] However, although there are elegant and creative azomethine-ylideinvolved cycloaddition reactions toward the construction of five-membered pyrrolidine architectures, [1,2] the direct catalytic asymmetric approach to enantioenr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(20 citation statements)
references
References 66 publications
0
20
0
Order By: Relevance
“…Using imine esters 153 as three-atom units (Fig. 3), (a) five-membered heterocyclic compounds (e.g., pyrrolidines) can be acquired by [3 + 2]-cycloaddition with twoatom dipolarophiles (e.g., electron-deficient alkenes); 308 (b) fused and bridged six-membered piperidines can be acquired via [6 + 3]-cycloaddition reactions of 6-π dipolarophiles (e.g., fulvenes, 2-acyl cycloheptatrienes, tropone) with azomethine, [309][310][311] while six-membered heterocyclic frameworks can be acquired by cross 1,3-dipolar [3 + 3]-cycloaddition of azomethine with pyrazolidinium ylides; 312 and (c) seven-membered heterocyclic azepines can be acquired from methyl coumalate via tandam [4 + 3]-cycloaddition/decarboxylation/isomerization. 308 By changing the chain length of the employed substrates, other five, six, seven, and eight membered N-heterocycles are obtained using appropriate catalysts or catalytic systems.…”
Section: N-heterocycles With Controllable Ring Size/typementioning
confidence: 99%
“…Using imine esters 153 as three-atom units (Fig. 3), (a) five-membered heterocyclic compounds (e.g., pyrrolidines) can be acquired by [3 + 2]-cycloaddition with twoatom dipolarophiles (e.g., electron-deficient alkenes); 308 (b) fused and bridged six-membered piperidines can be acquired via [6 + 3]-cycloaddition reactions of 6-π dipolarophiles (e.g., fulvenes, 2-acyl cycloheptatrienes, tropone) with azomethine, [309][310][311] while six-membered heterocyclic frameworks can be acquired by cross 1,3-dipolar [3 + 3]-cycloaddition of azomethine with pyrazolidinium ylides; 312 and (c) seven-membered heterocyclic azepines can be acquired from methyl coumalate via tandam [4 + 3]-cycloaddition/decarboxylation/isomerization. 308 By changing the chain length of the employed substrates, other five, six, seven, and eight membered N-heterocycles are obtained using appropriate catalysts or catalytic systems.…”
Section: N-heterocycles With Controllable Ring Size/typementioning
confidence: 99%
“…Pentafulvenes can react as 2π components with moderately electron-deficient dienes and 4π components in reactions with dienophiles (Scheme 5), whereas pentafulvenes substituted with EDG (e.g., NMe 2 ) at the exocyclic C6 position possess an increased electron density about the fulvene π-system, increasing the stability and hence nucleophilicity of the fulvene [29,73,96104]. This allows the fulvene to function as a 6π component in reactions with electron-deficient dienes (Scheme 5) and fulvenes acting as dipolarophiles have been reported for enantioselective [6 + 3] and [3 + 2] cycloadditions [8384 105]. In general, reactions with electron-rich alkenes will take place preferentially at the exocyclic C6 position while other less electron-rich species interact most strongly with the fulvene HOMO resulting in only [4 + 2] cycloadditions [101,103].…”
Section: Reviewmentioning
confidence: 99%
“…Furthermore, investigations of the possible effect of R 3 on the ester group revealed that big groups such as ethyl resulted in lower reactivity for this specific reaction although the enantioselectivity remained comparable (Table S3, entry 10). The corresponding ligand in optically pure form can be prepared by using preparative HPLC on a chiral stationary phase for racemate separation on gram scale or by using a known enantioselective [6+3] cycloaddition . With this optically pure ligand in hand, we investigated the importance of the protective group on the secondary amine.…”
Section: Figurementioning
confidence: 99%